STRUCTURAL RELIABILITY OF TRACTION INVERTER FOR MULTI-SYSTEM ELECTRIC LOCOMOTIVE WITH ASYNCHRONOUS TRACTION MOTORS - Muha, A. M. (Science and Transport Progress, 2009)
In the article the structural reliability of different variants of structured schemes of the steady-state converter for traction drive of promising multi-system electric locomotives with asynchronous traction engines is compared.